Etiological Evaluation of Acute Confusional State in Elderly (≥60 Years) Patients (Journal of Medicine, 2021)
Background: Acute confusional state or delirium is a frequent cause of hospital admission in the elderly. It is characterized by an acute fluctuating impairment of cognitive functions and inattention. Recognition and prompt treatment is crucial to decrease the morbidity and mortality of hospitalized elderly patients. Aim of this study was to evaluate the distribution of common medical conditions related to acute confusional state among elderly hospitalized Patients.Methods: This was a cross sectional study. We enrolled 380 patients from different medicine wards in Dhaka Medical College Hospital. We included patients with acute confusional state/delirium of less than 7 days duration. The enrolled patients fulfilled the diagnostic criteria of an acute confusional state. A predesigned checklist was used for data collection. Head injury was excluded by history and CT scan of brain. Patients with preexisting illnesses, such as dementia, psychiatric illnesses and recurrent seizures, and any case of poisoning was excluded. All findings were noted and recorded. A written informed consent was taken from the attendant and relatives.Result: Among 380 patients, most of confusional state developed after the age of 65 years and the mean age was 69 +/-7.6 years. Associated medical conditions were uncontrolled hypertension (63.2%), fever & infection (41.6%), uncontrolled DM (36.6%), CVD (28.4%), CKD & electrolytes abnormalities (10.5%), joint diseases & pain (13.7%). Most of the patients used plyphormacy (76.6%) out of which antihypertensive (60%) were common. The mean duration of presentation was 6.1+/-0.6 days, and among all patients about 63.7% were improved, 29.50% was in persistant symptom of confusion and 6.8% of them died.Conclusion: Acute confusional state was common after 65 years. Uncontrolled hypertension, fever & infection, uncontrolled diabetes, CVD, CKD & electrolytes abnormalities and polypharmacy were found commonly in patients with acute confusional state.J MEDICINE JAN 2021; 22 (1) : 41-45